Analisa Ketebalan Steam Chest sebagai Fungsi Breakthrough Time pada Steam Injection Process - Wibowo Wibowo; Lela Widagda; Dilla Fadhillah Hendri (Seminar Nasional Teknik Kimia Kejuangan, 2016)
The thickness of steam chest is found by integrating the steam velocity with respect to breakthrough time. The bigger rate of steam injection would form the thinner steam chest, which has affected to the cost required to production of steam that would be injected to the reservoir. There is a difference between the theoretical breakthrough time and steam chest calculations with the actual field situation. The difference occurs because in the theory used the ideal condition in which the heat efficiency is perfect, but in the actual field, there are many factors that cause the heat efficiency such as the slope of layers, reservoir heterogeneity, pressure gradient, and permeability distribution.